Pengaruh Bauran Pemasaran terhadap Volume Pembelian Produk Kopi Bubuk Robusta PT. Relolara Kabupaten Flores Timur - Marianus Mayolis; Mario Malado (Agriculture - Jurnal Ilmu Pertanian, 2024)
This research was conducted at PT. Rerolara Hokeng, Hokeng Village, Wulanggitang District, East Flores Regency. This research location was chosen because this area is the largest robusta coffee producer in Flores. Respondents were selected using the Malhotra approach, with 55 respondents. The analysis used by the researcher was multiple linear regression analysis. Data processing was performed using SPSS, and testing was carried out using the F test, t test, and analysis of determination. The results of the research data analysis show: 1) The partial regression test (t test) shows that only 6 independent variables are significant, while 5 independent variables are insignificant. 2) The F test results indicate that all independent variables simultaneously influence the independent variable (purchase volume). All independent variables are declared to have a simultaneous effect because the calculated F > F table ratio. 3) The R2 test results indicate a contribution of 91.2% of the independent variables, with an R value of 0.955. 4) Multiple linear regression analysis revealed several variables that significantly influence purchase volume. These variables include brand (X11), packaging size (X12), product quality (X14), halal label (X15), discounts (X22), price diversity (X23), and number of products (X31).